2020
DOI: 10.1093/medlaw/fwaa026
|View full text |Cite
|
Sign up to set email alerts
|

Disability Rights During COVID-19: Emergency Law and Guidelines in England

Abstract: Disabled people may be disproportionately impacted by the response to the COVID-19 outbreak because of the kinds of countermeasures needed to tackle it, and serious disruptions to the services on which they rely. There are reports from the disability community in England and elsewhere that measures taken to contain the spread of COVID-19 impact negatively on their human rights and experiences. This commentary focuses on the healthcare and social care systems in England and describes how laws and practices have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…Among children with IDDs, 30% within the USA and 50% outside the USA lost all rehabilitative services (67). A French survey revealed that 77% of children with physical disabilities experienced cancelled or postponed medical consultations during the pandemic (12). A study by Negrini et al (68) estimated that in Europe, more than one million people per day were being denied their rehabilitation services in acute, post-acute and outpatient settings.…”
Section: Barriers For Pwd During the Pandemicmentioning
confidence: 99%
“…Among children with IDDs, 30% within the USA and 50% outside the USA lost all rehabilitative services (67). A French survey revealed that 77% of children with physical disabilities experienced cancelled or postponed medical consultations during the pandemic (12). A study by Negrini et al (68) estimated that in Europe, more than one million people per day were being denied their rehabilitation services in acute, post-acute and outpatient settings.…”
Section: Barriers For Pwd During the Pandemicmentioning
confidence: 99%
“…This focus has disastrous effects when disabled people get subjected to utilitarian calculations. 3 Looking at the guidelines for allocation of medical resources in the UK, (Antova 2020 : 815) has made the point that ‘there are instances in the NICE and BMA guidelines that allow for unequal treatment to potentially take place disguised as an attempt to prioritise insufficient resources, or as a utilitarian concern for maximising health outcomes for that part of the population considered healthier (having a higher chance to survive or benefit from treatment)’. The COVID‐19 DRM report has also revealed and criticised the allocation of limited medical resources during medical triage for discriminating against disabled people: “Several written testimonies from Canada, the UK, the USA, Austria, Luxembourg, the Netherlands, Georgia, France, and South Africa said that their governments indicated that hospital triage should discriminate against COVID‐19 patients with disabilities in the event of a shortage of hospital places.…”
Section: Access To Health Carementioning
confidence: 99%
“…Our point of departure is the general observation that throughout the world, responses to COVID‐19 have been disability‐exclusive rather than disability‐inclusive. Disability injustices associated with COVID‐19 policies have included inaccessibility of public information and communications, inaccessibility of hygienic facilities, reductions in community supports (including personal assistance), enhanced institutionalisation and harms inflicted on disabled people in residential institutions, shortages of support staff, lack of access to food, medicines and essential supplies, ableist microaggressions and violence in public (including harassment and abuse), and discrimination in provision of health care (Antova, 2020 ; Brennan et al, 2020 ; Morris, 2021 ; Safta‐Zecheria, 2020 ; Shakespeare et al, 2021 ). We argue that these injustices have been underpinned by individualised and medicalised understandings of vulnerability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations